PENGARUH ORIENTASI ETIKA TERHADAP SENSITIVITAS ETIKA AUDITOR DENGAN KOMITMEN PROFESIONAL DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Pada Auditor KAP di Kota Semarang) - Dani Adi Kurniawan; Indira Januarti (Diponegoro Journal of Accounting, 2013)
The aim of this research is to provide empirical evidence about the effects of idealism andrelativism of ethics orientation of professional commitment and the commitment of theorganization. In addition, this research is try to give empirical evidence about the effects ofprofessional commitment to organizational commitment. Furthermore, To provide empiricalevidence about the effects of idealism and relativism of ethics orientation, professional commitmentand also ethical sensitivity of organizational commitment.Population in this research are auditors who work in the public accountant office inSemarang. The number of samples obtained by using convenience sampling technique are 45respondents. The kind of data used is primary data. Furthermore, collecting data method used iscollecting data method by using questionnaire.The results of research using the PLS are : idealism and relativism influence significantly toprofessional commitment , Idealism significantly influence to organizational commitment, whereasrelativism does not significantly influence to organizational commitment. Professionalcommitments take effect insignificantly to the to organizational commitment. Idealisms, relativism,and the Organizational commitment take effect to ethical sensitivity, whereas professionalcommitment does not influence significantly towards ethical sensitivity. The influence ofintervening of idealism towards ethical sensitivity through professional commitment is notaccepted. The influence of intervening of idealism towards ethical sensitivity throughorganizational commitment is accepted.